Characteristics of Kedondong Trass and Bobos Trass as Cement Raw Material, Cirebon, West Java, Indonesia - Jenian Marin; Tri Winarno; Shofiana Nadia Fairuz (UIR PRESS, 2022)
The use of cement materials in construction continues to increase every year, consumes lots of raw material and emits CO2 from clinker production. To eliminate this negative effect, alternative materials are needed. Trass is natural pozzolan which is formed from silica-alumina rich volcanic rocks. As supplementary cementitious material, trass is sufficiently durable and reduce clinker proportion in cement mixture, thus more environmentally friendly. This research aims to determine characteristics and composition of Kedondong trass and Bobos trass, Cirebon, West Java as raw material for pozzolan cement. The study was conducted using petrography and XRD analysis to determine mineralogy of rocks. XRF analysis was carried out to determine chemical composition as well as other tests to determine trass quality. Kedondong trass is originated from andesite intrusion and andesitic breccia, while Bobos trass is formed from hypersthene-andesite intrusion. Based on mineralogy analysis, trasses have similar mineral composition consist of plagioclase, quartz, pyroxene, hornblende, and sanidine. XRD analysis shows abundance of cristobalite and tridymite from each samples. This mineralogy is confirmed by geochemistry result, which is the samples contain more than 70% SiO2 + Al2O3 and less than 4% SO3. Other chemical characteristics that have been tested are moisture content, ignition loss, and clay content in which all of those parameters meet the industrial standard for cement material.